PET/SPECT Test Phantom - Shah, Sayed Inayatullah (2010)

(untitled)
It is vital to test the response, reliability and to determine image artifacts produced by the nuclear medicine tomography systems due to some systemic limitations before their use in clinical studies. That cannot be reliably achieved by scanning patients. Different types of test phantoms are commercially available with accurately/precisely known composition, which helps in acquiring prior knowledge about the capability and drawbacks of a nuclear medicine tomography system. A cold regions insert, that can be placed into a cylindrical tank of a commercially provided PET/SPECT phantom has been developed (for R A Carlson’s phantom - which consists, hot, cold and linearity inserts where the hot regions insert is comprised on a “V” shaped eight pairs of various sized holes with a cold background). The new produced cold regions insert, consists solid plastic rods, 5 cm long (each) with same diameters and exactly the same arrangement as hot region holes pairs insert of R A Carlson’s phantom. Both inserts have been attached with each other by aligning hot and cold regions for similar cross sectional views. The data acquired by this arrangement provides a simple way for measurement and comparison of the performance of a system i.e., image resolution in terms of position and size of hot and cold regions in the phantom, region(s) detectability. Also the accuracy of scatter, attenuation correction and image reconstruction techniques in nuclear medicine tomography may be tested.